(untitled) (Revista de História Regional, 2020)
Between the 1930s and 1940s, the expansion of the agricultural and demographic frontier to Central Brazil foresaw the creation of zones producing raw materials (hinterland) to supply agricultural goods to the “central” regions of the country. At the same time, it sought to create urban centers to integrate both the economy and culture of the time. Based on the creation of urban centers in the Brazilian hinterland in this period, this article proposes to analyze the city of Goiânia, the new capital of Goiás. Created in the 1930s, it has historically been part of this project, being considered by the Estado Novo (1937-1945) as an urban symbol of the march to the West. Based on the theoretical and methodological assumptions of urban and environmental history, we aim to analyze urban projects for green areas in the new capital, and the transformations of these spaces as a result of the land expansion of the original project. The results indicate that starting in the 1940s, progressive urbanism, which guided the creation of Goiânia, lost strength as the interests of speculative capital became more powerful and the state government became weaker. These changes caused a reduction of green spaces and an expansion of land and properties that transformed the landscapes of the new capital of Goiás.